Compressive Strength and Water Absorption of Concrete Containing Ground Coal Bottom Ash as Partial Cement Replacement - Nabilla, Mohamad; Khairunisa, Muthusamy; Budiea, A. M. A.; Rahimah, Embong; Tanash, Alaa Omar (2022)
Growing coal consumption at power plants due to the rising demand for energy results in coal bottom ash waste generation. The disposal of this ash at landfills is consume space and poses a risk of pollution to the environment. Channelling this waste to produce blended cement would reduce the consumption of raw materials from nature and decrease greenhouse gas releases. This research aims to investigate the effect of ground coal bottom ash (GCBA) as partial cement replacement on compressive strength and water absorption of concrete. The proportion of coal bottom ash integrated ranges from 0%, 10%, 20%, 30%, and 40% (by weight of binder). All specimens were water-cured until the testing day. Integration of 10% coal bottom ash produces concrete with enhanced compressive strength. The presence of silica has enabled the occurrence of pozzolanic reactions that contribute to the well-packed internal structure of concrete with enhanced compressive strength and lower water absorption. Success in utilizing coal bottom ash for cement production would reduce the harvesting of limestone from the environment and waste disposed of at landfills.